Workplace cyberbullying and creativity: examining the roles of psychological distress and psychological capital. Issue 4 (11th November 2020) - Kalyar, Masood Nawaz; Saeed, Munazza; Usta, Aydin; Shafique, Imran
Abstract : Purpose: This study aims to investigate the effects of workplace cyberbullying on creativity directly and through psychological distress. Furthermore, this study proposes that psychological capital (PsyCap) buffers the harmful effects of workplace cyberbullying on psychological distress and creativity. Design/methodology/approach: The data were collected in two waves from 329 nurses working in four large public hospitals located in a metropolitan city of Pakistan. The data were analyzed through PROCESS (Model 8) using SPSS. Findings: The results demonstrate that cyberbullying negatively affects creativity through increased psychological distress. The findings also explicate that PsyCap moderates the effects of cyberbullying on psychological distress such that the link was weak (vs strong) for those (victims) who had high (vs low) PsyCap. Practical implications: This study recommends management to develop and promote PsyCap among employees because these positive resources help them to regulate their emotions and cognition to overcome negative consequences of cyberbullying and other workplace stressors. Originality/value: Psychological distress as an underlying mechanism between cyberbullying and creativity as well as buffering effect of PsyCap is the novelty of the study.